Resuscitation training of paediatricians. Issue 2 (1st February 2003) - Jewkes, F; Phillips, B
Abstract : Intensive, didactic courses teaching resuscitation training are currently not only very popular, but are also required curricula content for certain aspects of medical training. There are a number of such courses available in the field of paediatrics, each with a different emphasis and target audience. They are not inexpensive, as they utilise large amounts of training equipment and have a high instructor to student ratio. This review will examine the course structures, instructor training, the need for such courses, and effect they may have on patient outcome.